PsycEXTRA Dataset 2012
DOI: 10.1037/e656072012-001
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Mental Health Stigma and Discrimination in a Mexican American Sample

Abstract: The stigma of mental health problems between Mexican Americans and White non-Hispanic European Americans was investigated and measured by attitudes toward seeking help and the amount of social distance desired from individuals with mental health problems. The stigma of mental health has been identified as a barrier to accessing mental health services among Mexican Americans and men in general. Men from both groups access mental health services at a significantly lower rate than women from both groups. This stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 73 publications
(144 reference statements)
0
5
0
Order By: Relevance
“…Results of the factor analysis in the Interian et al (2010) study indicated support for Social Distance Scale, SCMHC, and LSAS as single-factor measures. The factor analysis conducted by Wright (2009) demonstrated different factor solutions for the SSOSH for the White, non-Hispanic European American sample compared to the Mexican American sample, indicating that Hispanic participants may respond differently to these items compared to non-Hispanic, White participants. Both studies used English and Spanish versions of the scales but neither differentiated by language in their analyses.…”
Section: Resultsmentioning
confidence: 93%
See 3 more Smart Citations
“…Results of the factor analysis in the Interian et al (2010) study indicated support for Social Distance Scale, SCMHC, and LSAS as single-factor measures. The factor analysis conducted by Wright (2009) demonstrated different factor solutions for the SSOSH for the White, non-Hispanic European American sample compared to the Mexican American sample, indicating that Hispanic participants may respond differently to these items compared to non-Hispanic, White participants. Both studies used English and Spanish versions of the scales but neither differentiated by language in their analyses.…”
Section: Resultsmentioning
confidence: 93%
“…Of the eight studies that administered scales in Spanish, six reported on the translation process of the scales. Three studies used a backtranslation process (Dueweke & Bridges, 2017; Keeler & Siegel, 2016; Wright, 2009) and two studies (Hernandez & Organista, 2013; Unger, Cabassa, Molina, Contreras, & Baron, 2013) used translations from the Interian et al (2010) study that were developed by a bilingual research assistant and checked by two researchers. Sample sizes of the studies ranged from 80 to 267 Hispanic adults, with a majority (57%) of the 2507 total participants being college/adult school students.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…While the use of existing measures may be preferable to the development of new measures [18], steps should be taken to assure that measures are linguistic and culturally relevant for use with new populations [24]. Previous research on stigma measurement among Hispanics has emphasized the need for this type of validation, with one study reporting different factor structures for a measure tested in both a Hispanic and non-Hispanic, White sample [25] and another study concluding a lack of support for a previously validated measure when it was tested with a primarily Spanish-speaking sample [8].…”
Section: Introductionmentioning
confidence: 99%